2001
DOI: 10.1080/09603120020019674
|View full text |Cite
|
Sign up to set email alerts
|

Decanting versus sterile pre-filled nutrient containers ‐ the microbiological risks in enteral feeding

Abstract: A simulated ward study was carried out to compare the microbiological risk of assembling and running four different enteral feeding systems for 24 h. Assembly was carried out, (i) according to manufacturers' instructions with hands either covered by disposable gloves or deliberately contaminated with a test organism, or (ii) touching both the nutrient container top and pump set connector with hands deliberately contaminated with K. aerogenes. Two of the systems were ready-to-hang types (pack and bottle), the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…16,23,45 In an early study of various administration sets that were deliberately contaminated, investigators found sterile, decanted formula to have low-to-no bacterial contamination for up to 12 hours when clean gloves were worn when adding the formula to the bag. 58 They also found that a recessed spike set allowed for limited exposure of the portto-touch contamination, regardless of the type of container used. Weenk and Kemen compared various feeding systems and found a sterile glass bottle containing enteral formula to be associated with the lowest level of microbial growth from touch contamination.…”
Section: 56mentioning
confidence: 98%
See 4 more Smart Citations
“…16,23,45 In an early study of various administration sets that were deliberately contaminated, investigators found sterile, decanted formula to have low-to-no bacterial contamination for up to 12 hours when clean gloves were worn when adding the formula to the bag. 58 They also found that a recessed spike set allowed for limited exposure of the portto-touch contamination, regardless of the type of container used. Weenk and Kemen compared various feeding systems and found a sterile glass bottle containing enteral formula to be associated with the lowest level of microbial growth from touch contamination.…”
Section: 56mentioning
confidence: 98%
“…Many studies in the literature document the safety of a 24-hour hang time for sterile closed systems. 24,30,32,45,58 A few studies looking at hang times of 36 and 48 hours have reported little to no contamination. 24,58,59 One study even validated the safety of using a closed system enteral formula for intermittent bolus feeding in nursing home patients.…”
Section: 56mentioning
confidence: 99%
See 3 more Smart Citations